Mediasi Sekuensial Sosial Media dan Digital Marketing pada Hubungan Brand Ambassador dengan Brand Trust Produk Scarlett Whitening - Rahayu Lestari; Beladdina An’nisa (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to examine the sequential mediation of the relationship between brand ambassadors and trust. Sequential mediation consisting of digital marketing and Instagram social media. The target population in this study are Scarlett Whitening product customers who use Instagram who are students of a private university in Jakarta. A sample of 96 was measured based on the rule of thumb of the experts The sampling technique used is convenience sampling. The method used in the research to test mediation uses a process macro with model no 6. Tests of validity, reliability and correlation are also described. The results show that brand ambassadors have an effect either directly or indirectly through sequential mediation (digital marketing and social media) on customer trust. Suggestion. Companies must be able to choose brand ambassadors who have good credibility because this not only has a direct effect on trust but also affects trust through increasing customer perceptions of digital marketing and social media used.